Bishops in Flight : Exile and Displacement in Late Antiquity (2019)
Flight during times of persecution has a long and fraught history in early Christianity. In the third century, bishops who fled were cowards or, worse yet, heretics. On the face of it, it meant denial of Christ and thus betrayal of the faith and its community. But, by the fourth century, the terms of persecution changed as Christianity became the favored cult of the Roman Empire. Prominent Christians who fled and hence survived became founders and influencers of Christianity over time. Bishops in Flight examines the various ways these episcopal leaders both appealed to and altered the discourse of Christian flight to defend their status as purveyors of Christian truth even when their exiles appeared to condemn them. It illuminates how profoundly Christian authors deployed theological discourse and the rhetoric of heresy to respond to the phenomenal political instability of the fourth and fifth centuries.